Assessment of Certain Summer Management Practices on Cortisol and Physiological Response of Crossbred Calves - A. L. Nayak; M. M. Trivedi (Newest Updates in Agriculture and Veterinary Science Vol. 1, 2022)
The presented study on certain summer management practices on performance on crossbred calve. To estimated heat stress in crossbred calves during the summer seasons at livestock research station Anand, Anand agricultural university. During experiment, 18 crossbred calves were divided into two group: control (T1) and white painted roof with applied fogger (T2). The Meteorological data were recorded at 7:30 a.m. (morning), 2:30 p.m. (afternoon) and 7:30 p.m. (evening). Microclimate includes ambient temperatures, Relative humidity, air flow and light intensity. The found that ambient temperature at 2:30 p.m. was significantly lower in T2 Group as compared to control group. Relative humidity at 2:30 p.m. was significantly higher in T2 group as compered to T1 group. The average cortisol level of T1 and T2 group was 9.97 ± 1.285 and 8.43 ± 0.389. Cortisol level and physiological responses found significantly lower in T2 group as compared to control group. Climatic factors such as temperature, humidity, rainy days and sunshine hours are known to influence the milk production. Similarly seasonal and yearly variations in milk production are mainly due to difference in the climatic attributes. There is a need to know more about relationship of the climatic attributes with production traits in cow It will help to plan managemental appropriate to each season. During summer (May-June). The atmospheric temperature goes as high as 45\(^°\)C during day time and 30\(^°\)C during night and photoperiod extends up to 12-14 hours. Dairy animal s are homeotherms and therefore. When the environmental temperature rises or falls abnormally, the animals are put to different types of stress resulting from the quality of feed and physical environment. This assessment to know effect of summer management practices on growth performance of crossbreed calves, feed consumption and feed efficiency and effect of macro-micro climate on calves.